2017
DOI: 10.1111/vsu.12649
|View full text |Cite
|
Sign up to set email alerts
|

Major complications of tibial tuberosity advancement in 1613 dogs

Abstract: Major complications after TTA are uncommon, even in dogs with concurrent patellar luxation or bilateral simultaneous procedures. In spite of its morbidity, medial meniscal release may prevent postliminary meniscal tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 30 publications
(134 reference statements)
5
50
0
4
Order By: Relevance
“…The occurrence of SSI in this study was similar to that in previously reported studies . Although our definition of SSI was based on that defined by the CDC, previous studies may not have used such criteria.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The occurrence of SSI in this study was similar to that in previously reported studies . Although our definition of SSI was based on that defined by the CDC, previous studies may not have used such criteria.…”
Section: Discussionsupporting
confidence: 88%
“…Our reported requirement for TTA implant removal was similar to that in previously reported studies of 0%‐1.3% . Most (62.5%) cases of implant removal in our study did not have cage removal performed, and only three cages that were initially left in place after plate removal required removal at a later date.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations